ISOLATION OF LACTIC ACID BACTERIA FROM PICKLED CABBAGE FOR PROBIOTIC PROPERTIES - Dangmanee, Nattakan; Chumkeaw, Naruemon; Munkhun, Rujira; Boonson, Jariya (Interprofessional Journal of Health Sciences, 2023)
The aims of the present study were to isolate the probiotic lactic acid bacteria from pickled cabbage using physical and biochemical characteristics tests, i.e. Gram stain, catalase and oxidase test. After that, all isolates were evaluated the probiotic properties as acid-base resistance, bile salt resistance and inhibitory effect against gastrointestinal pathogenic bacteria. It was found that 6 isolates were Gram-positive, catalase negative and oxidase negative bacteria. All isolates were resistant to pH 2-4 and 0.1-0.3% bile salt and inhibited Enteropathogenic Escherichia coli DMST 30546.